Characterization of flagellins isolated from a highly motile strain of Lactobacillus agilis - Kajikawa, Akinobu (BMC Microbiol, 2016)
BACKGROUND: Most lactic acid bacteria are non-motile but some of them are flagellated and exhibit motility. So far, motile lactobacilli have rarely been studied, and characteristics of their flagellins are poorly understood. In this study, a highly motile strain of Lactobacillus agilis was recruited for transcriptional analysis and characterization of its flagellins. RESULTS: Unlike another motile lactic acid bacteria of intestinal isolate, Lactobacillus ruminis, flagellar filaments of the L. agilis strain probably consist of two homologous but distinct flagellins. Glycosylation of the flagellar filaments and their resistance to heat, acid and SDS were also observed. The immunological activity of the flagellins was evaluated through the stimulation of Caco-2 cells. The results show that TLR5-stimulating activity of the protein is attenuated, likely due to an incomplete TLR5-recognition site. CONCLUSIONS: The flagella filaments of L. agilis BKN88 consist of two homologous glycosylated flagellins, which likely have an incomplete TLR5-recognition site. The characteristics of the flagellin are presumably a consequence of adaptation as a commensal microbe in the gastrointestinal tract.